Squamous Cell Carcinoma Arising from a Morel-Lavallée Lesion: A Case Report. Issue 4 (October 2019) - Mills, Emily S.; Debbi, Eytan M.; Brien, Earl W.; Giaconi, Joseph C.; Moon, Charles N.
Abstract : Case: A 72-year-old man presented 20 years after a Morel-Lavallée (ML) lesion with pain and drainage. Biopsies of the lesion and lymph nodes were positive for squamous cell carcinoma (SCC). There was no cutaneous involvement or distant metastasis. After chemotherapy and radiation, he underwent resection of the lesion and lymph nodes with flap closure. Two months postoperatively, he unfortunately developed malignant pleural effusions, hypercalcemia, and kidney injury and was eventually transferred to hospice care and died. Conclusion: This is the first report of SCC arising from a ML lesion. Chronic ML lesions should be treated aggressively and monitored for transformation into malignancy, even without cutaneous involvement.